More about seat racing for selection - Kleshnev, V. (BioRow, 2021)
We have previously discussed seat racing (RBN 2013/06) and found that "fair seat racing is not possible in one boat only. It should be done between two or more boats racing one against another, so weather conditions and fatigue would affect all rowers similarly." Also, an objective seat race must be performed without "preselected" rowers, otherwise, it could just be a conscious or subconscious vote for crewmates. The conclusion was: "Objective selection for big boats must be done based on performance in standard races over 2km in small boats (singles and pairs)."